Helically Assembled Pyrene Arrays on an RNA Duplex That Exhibit Circularly Polarized Luminescence with Excimer Formation. Issue 27 (6th June 2016) - Nakamura, Mitsunobu; Suzuki, Junpei; Ota, Fuyuki; Takada, Tadao; Akagi, Kazuo; Yamana, Kazushige
Abstract: Circularly polarized luminescence (CPL) was observed in pyrene zipper arrays helically arranged on an RNA duplex. Hybridization of complementary RNA strands having multiple (two to five) 2′‐ O ‐pyrenylmethyl modified nucleosides affords an RNA duplex with normal thermal stability. The pyrene fluorophores are assembled like a zipper in a well‐defined helical manner along the axis of RNA duplex, which, upon 350 nm UV illumination, resulted in CPL emission with pyrene excimer formation. CPL ( g lum ) levels observed for the pyrene arrays in dilute aqueous solution were +2×10 −2 –+3.5×10 −2, which are comparable with | g lum | for chiral organic molecules and related systems. The positive CPL signals are consistent with a right‐handed helical structure. Temperature dependence on CPL emission indicates that the stable rigid RNA structure is responsible for the strong CPL signals. The single pyrene‐modified RNA duplex did not show any CPL signal. Abstract : Circularly polarized luminescence (CPL) can be observed in pyrene zipper arrays that are helically arranged on an RNA duplex. This provides important insight for the development of CPL‐based biosensing and bioimaging using fluorophore‐modified nucleic acid sequences.